Finite-difference time-domain modeling of transient infrasonic wavefields excited by volcanic explosions - Kim, K.; Lees, J.M. (Blackwell Publishing Ltd, 2011)
Numerical modeling of waveform diffractions along the rim of a volcano vent shows high correlation to observed explosion signals at Karymsky Volcano, Kamchatka, Russia. The finite difference modeling assumed a gaussian source time function and an axisymmetric geometry. A clear demonstration of the significant distortion of infrasonic wavefronts was caused by diffraction at the vent rim edge. Data collected at Karymsky in 1997 and 1998 were compared to synthetic waveforms and variations of vent geometry were determined via grid search. Karymsky exhibited a wide range of variation in infrasonic waveforms, well explained by the diffraction, and modeled as changing vent geometry. Rim diffraction of volcanic infrasound is shown to be significant and must be accounted for when interpreting source physics from acoustic observations.